Artificial joints - Ventura, Marne (Engineering the human body., 2020)
Investigates the power of modern artificial joints to aid and improve the lives of people with joint deterioration. Discusses new technology that has made replacement joints more effective, useful, and comfortable than ever. Includes a glossary, an index, resources for further information, and text-dependant questions.